Demonstration of Use of High-Performance Lightweight Concrete in Bridge Superstructure in Virginia - Waldron, Christopher J; Cousins, Thomas E; Nassar, Adil J; Gomez, Jose P (Journal of performance of constructed facilities, 2005)
The general objective of this research was the construction and evaluation of a bridge using high-performance lightweight concrete (HPLWC). The resulting bridge over the Chickahominy River near Richmond, Va., consists of 15 prestressed American Association of State Highway and Transportation Officials (AASHTO) Type IV girders made of HPLWC with a density of 1,920 kg∕ m3 and a minimum required 28-day compressive strength of 55 MPa . The bridge also has a lightweight concrete (LWC) deck with a density of 1,850 kg∕ m3 and a minimum required 28-day compressive strength of 30 MPa . This research study is chiefly concerned with investigating the effects of using lightweight concrete in prestressed girders on transfer length, development length, flexural strength, girder live-load distribution factor, and dynamic load allowance. Transfer length was determined to be 432 mm , or 33 db , for several girders at the time of prestress transfer. The development length was determined to be between 1,830 and 2,440 mm , while the flexural strength ranged from 11 to 30% higher than the AASHTO flexural capacity. The measured distribution factors and dynamic load allowance were smaller than the AASHTO standard and LRFD values.